An Analytical Study On The Investment Pattern And Savings By Working Women In Relation To The Retirement Corpus Post Retirement (International Journal of Food and Nutritional Sciences, 2022)
Investment is the way to utilise savings which are kept idle. The motive of doing investment is to get wealth maximisation or regular return or both. While doing investment one is concern about safety of money with profit. Majority of working women are doing investment after taking information from various sources. The investment process is done by themselves or by someone else. When the investors choose the investment avenues, they take into consideration various factors such as risk, return, time etc. Factors are the features which lead any activity. In case of investment there are many factors which govern the decision of investment. These factors are social, economic, cultural and sometime behavioural. Studying, exploring and understanding the factors, helps to determine the investment behaviour of one. Investment is the way to have financial growth. Factors of investment are different in different gender i.e. men and women. In case of women investor the factors are mainly dominated by social and cultural one. Women investors in large do not take risk while doing investment. And in case of financial planning for retirement there are no efforts take for it.